Effectiveness and efficiency of search methods in systematic reviews of complex evidence: audit of primary sources. Issue 7524 (17th October 2005) - Greenhalgh, Trisha; Peacock, Richard
Abstract: Objective To describe where papers come from in a systematic review of complex evidence. Method Audit of how the 495 primary sources for the review were originally identified. Results Only 30% of sources were obtained from the protocol defined at the outset of the study (that is, from the database and hand searches). Fifty one per cent were identified by "snowballing" (such as pursuing references of references), and 24% by personal knowledge or personal contacts. Conclusion Systematic reviews of complex evidence cannot rely solely on protocol-driven search strategies.